Cross-Border Quest: The Reality and Legality of Transplant Tourism - Frederike Ambagtsheer; Damián Zaitch; René van Swaaningen; Wilma Duijst; Willij Zuidema; Willem Weimar (Journal of Transplantation)
Background. Transplant tourism is a phenomenon where patients travel abroad to purchase organs for transplants. This paper presents the results of a fieldwork study by describing the experiences of Dutch transplant professionals confronted by patients who allegedly purchased kidney transplants abroad. Second, it addresses the legal definition and prohibition of transplant tourism under national and international law. The final part addresses the legal implications of transplant tourism for patients and physicians. Methods. The study involved seventeen interviews among transplant physicians, transplant coordinators and policy-experts and a review of national and international legislation that prohibit transplant tourism. Results. All Dutch transplant centers are confronted with patients who undergo transplants abroad. The estimated total number is four per year. Transplant tourism is not explicitly defined under national and international law. While the purchase of organs is almost universally prohibited, transplant tourism is hardly punishable because national laws generally do not apply to crimes committed abroad. Moreover, the purchase of organs (abroad) is almost impossible to prove. Conclusions. Transplant tourism is a legally complex phenomenon that warrants closer research and dialogue. The legal rights and obligations of patients and physicians confronted with transplant tourism should be clarified.